Censo de habitantes de calle y en calle de la ciudad de Medellín y sus corregimientos (2010)
ABSTRACT: The urban growth of Medellín has its more significant impact since the end of 60 years `s, in a continuous and unequal growth. Simultaneously, blunting the decade of 70´s, is accompanied of the metropolización phenomenon, because the Valley of Aburrá already concentrated 44% of the departmental total population, of which, the municipality of Medellín represented one third part of that metropolitan total. These changes, combined to the displacement of the population of their places of origin and to the social decomposition by the situation of conflict for several decades, have created propitious conditions for the increase of people in street situation, where they search carefully the subsistence in the public space. Thus, the city slowly went filling of people who lacked the most fundamental elements for the simple existence: work, food, a ceiling, etc. Briefly went filling of population in street situation, social sectors whose scope of subsistence is the street, either like unique space of work - the unmannerliness or, like life space. In fact, as or it were indicated in the reference terms that summoned the present census, "the population street inhabitant and in street, it has stopped being or considering themselves like an urban phenomenon, and situation becomes something so daily that it is part of the landscape, that far from to lessen itself grows and their characteristics have become like the city" and is added that the one became a constituent fact of the normal panorama of our cities that "some people or is by necessity and others like life style, (do) of the street its place of encounter and/or economic subsistence". By all means, it is easy to include/understand that the population in street situation, by only made turn the street into the scene and scope of subsistence, does not form a homogenous group: For some the street is a work place - they are informal works and even, the exercise of begging or circus activities and many illicit or other that generate income to him soon to return to their respective houses For others is even the unique vital space that they own, is its place of work, house, and still of recreation, that is to say, the street is it everything. For this reason, also the acceptance of which is current this population, denominated inhabitants in situation of street, this differentiated in two great groups, thus: - Inhabitant of the street: She is the person of any age, that generally, are broken completely the bonds with its family and make of the street its permanent space of life. - Inhabitant in the street: She is the person of any age, that does of the street the own scene for its survival and the one of its family, alternating the house, the school and the work in the street, are observed generally exerting begging, in circus spectacles, traveling sales, in recycling workings or exerting prostitution in the main economic runners of the city of Medellín, among others own activities of this population. It is important to stand out that they count on a place where to arrive: the house of its family, the room of a residence or a small hotel.